Kontribusi Usahatani Kakao terhadap Pendapatan Rumah Tangga Petani di Desa Pangsan, Kecamatan Petang, Kabupaten Badung - PARTIWI, ELTA DINA; BUDIASA, I WAYAN; WIDYANTARA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Contribution of Cocoa Farming to Farmers Household Income in Pangsan Village, Petang District, Badung Regency The study aims to determine the sources of cocoa farmers' income, and the large contribution of cocoa farming to the income of the farmers' households in Pangsan Village, as well as to find out the physical management practices and postharvest handling applied by the cocoa farmers. The technique of determining the sample was by using proportional random sampling and the sample was taken randomly to select the sample by lottery method with the number of samples of 34 cocoa farmers. The data collection was conducted from early February to the end of February 2017. The study used farming analysis to calculate net income and total household income of cocoa farmers during 2016. The results showed that cocoa farming has the highest contribution of 70.10% of the total household income of farmers amounting to Rp. 85,954,990.80 / year with an average income of Rp. 60,252,258 / year. The physical management practices of cocoa farming applied by cocoa farmers in Pangsan Village are in accordance with the physical management practices in the cocoa Good Agricultural Practices (GAP) guidelines, and it is known that farmers did not apply Good Handling Practices (GHP) to postharvest handling.